Fluid inclusion evidence for a Cretaceous-Palaeogene petroleum system, Kangerlussuaq Basin, East Greenland - Jonk, R.; Parnell, J.; Whitham, A. G. (Marine and Petroleum Geology, 2005)
Petrographic and fluid inclusion studies of sandstone samples from the Cretaceous–Palaeogene Kangerlussuaq basin reveal the presence of oil inclusions as secondary trails across grains. Fluid inclusion petrographic and microthermometric investigations suggest that oil was trapped at temperatures in excess of about 108 °C. Although due to deep burial (in excess of 6 km) and subsequent exhumation the Kangerlussuaq basin itself cannot be considered as prospective for petroleum, it provides a useful analogue for nearby basins on the North Atlantic margin. Given the fact that no sediments older than Aptian–Albian are present in the basin, a conventional upper Jurassic source rock can be ruled out. Oil may have been generated from an Aptian–Albian estuarine mudstone, whose potential as a regional source rock needs to be assessed. Oil inclusions also occur in injected sandstones that cross-cut the whole sedimentary section and these sandstones may have acted as conduits for petroleum migration. Their presence in offshore North Atlantic basins underneath the Tertiary basalts also needs to be considered in play concepts